Enacting Sonic-Cyborg Performance through the Hybrid Body in Teka-Mori and Why Should Our Bodies End at the Skin? - Hsu, Aurie; Kemper, Steven (Leonardo Music Journal, 2019)
In "A Cyborg Manifesto," Donna Haraway explores implications of the increasing hybridization of humans and machines. While society has long been concerned with the encroachment of technology onto human activity, Haraway challenges this concern, suggesting instead a kinship between organism and machine, a hybrid body. A sonic-cyborg performance realizes this understanding of the human-machine hybrid through movement and sound, incorporating a "kinesonic" approach to composition and an exploration of "mechatronic" expression. In this article, the authors describe their approach to enacting sonic-cyborg performance by outlining the creative framework and associated technologies involved in two collaborative pieces that explore questions of fluidity between organism and machine: Teka-Mori and Why Should Our Bodies End at the Skin?